Cultural differences in hydration practices among physically active individuals: a narrative review. Issue 1 (31st December 2022) - Leow, Clarence Hong Wei; Tan, Beverly; Miyashita, Masashi; Lee, Jason Kai Wei
ABSTRACT: It is well-established that appropriate hydration practices are essential in promoting health and optimizing performance and recovery. However, evidence-based hydration guidelines may not be adopted due to cultural differences across countries, such as religious beliefs, traditions, preferences, and beverage availability. Examples of hydration practices influenced by culture include beer consumption after sports in Western countries, consumption of sugarcane juice in India and Ramadan fasting among Muslims. For most cultural hydration practices, there is limited scientific evidence on their effects on rehydration, exercise performance, and recovery. Despite possible benefits of various hydration practices on exercise performance and recovery, they are inconsistent with current evidence-based hydration recommendations. More research on the impacts of cultural hydration differences on physiology, performance, and recovery is warranted to allow evidence-based guidelines and advisories. Abbreviations : ABV: alcohol by volume, ACSM: American College of Sports Medicine, NATA: National Athletic Trainers' Association, ROS: reactive oxygen species, TCM: Traditional Chinese Medicine